The Efficacy of a Home-School Intervention for Preschoolers With Challenging Behaviors: A Randomized Controlled Trial of Preschool First Step to Success. (September 2014) - Feil, Edward G.; Frey, Andy; Walker, Hill M.; Small, Jason W.; Seeley, John R.; Golly, Annemieke; Forness, Steven R.
The field of early intervention is currently faced with the challenge of reducing the prevalence of antisocial behavior in children. Longitudinal outcomes research indicates that increased antisocial behavior and impairments in social competence skills during the preschool years often serve as harbingers of future adjustment problems in a number of domains including mental health, interpersonal relations, and academic achievement. This article reports the results of a cross-site randomized controlled trial, in which 128 preschool children with challenging behaviors were assigned to either a Preschool First Step to Success (PFS) intervention (i.e., experimental) or a usual-care (i.e., control) group. Regression analyses indicated that children assigned to the Preschool First Step intervention had significantly higher social skills, and significantly fewer behavior problems, across a variety of teacher- and parent-reported measures at postintervention. Effect sizes for teacher-reported effects ranged from medium to large across a variety of social competency indicators; effect sizes for parent-reported social skills and problem behaviors were small to medium, respectively. These results suggest that the preschool adaptation of the First Step intervention program provides early intervention participants, staff, and professionals with a viable intervention option to address emerging antisocial behavior and externalizing behavior disorders prior to school entry.